Study on live load reduction factors of train for long span multitrack railway suspension bridges. (August 2021) - Li, Wenjie; Gong, Jinxin; Zhang, Xigang
Abstract: The reduction factor of live load of train for design of long span multitrack railway bridge is investigated as a parallel research program of design of the Wufengshan Yangtze River suspension bridge in China. Firstly, to simplify the calculation of cable force of the suspension bridge with higher geometry non-linearity, the force history curves of typical suspenders are developed in the simulation of random trains running on the railway on bridge. Secondly, the probabilities of the trains running on the multitrack railway crossing on the bridge are analyzed and the probability models of the force of key suspender is established by Monte-Carlo simulation based on the established suspender force history curves. Finally, the suspender force reduction factors for bridge with multitrack railway on it are determined in the sense of the same exceeding probability. The results indicate that the probability is small for the trains on different tracks crossing on bridge at the same time. The probability distribution of the maximum force of the key suspender within the design working life can be described by a combination of a weighted lognormal and a weighted normal distribution. For the two-, three- and four-tracks railway suspension bridge, the derived reduction factors of the suspender force or the live load of the trains are 0.90, 0.75 and 0.65, respectively. Comparing these factors with those specified in the China railway bridge design code reveals that the reduction factor for two-tracks railway bridge is the same, and somewhat smaller for the three- and four-tracks railway bridge.